LEGAL RESPONSIBILITY OF RACING EXHAUST WORKSHOP BUSINESS ACTORS FROM SADD AL-DZARI'AH'S PERSPECTIVE (CASE STUDY OF LETDA SUJONO STREET, MEDAN CITY) - Abdur Rahman; Abd. Rahman Harahap (Journal Analytica Islamica, 2026)
The widespread use of racing exhausts in urban areas has caused various social problems, particularly related to noise that disturbs public order and public comfort. This phenomenon is not only related to the behavior of motor vehicle users, but is also influenced by the activities of repair shops that provide non-standard exhaust installation services. This study aims to analyze the legal responsibilities of racing exhaust repair shops based on positive law and review these practices from the perspective of Sadd al-Dzari'ah in Islamic law. The study used an empirical juridical method with a qualitative approach through field observations, interviews with residents, law enforcement officers, and repair shop owners in the Letda Sujono Street area of Medan City. The results showed that approximately 20–30% of motorcyclists use racing exhausts with noise levels reaching 80–95 dB, while there are approximately 6–9 repair shops that have the potential to provide non-standard exhaust installation services. Law enforcement has so far focused on road users, so the responsibility of repair shop owners has not been optimally addressed. From the perspective of Sadd al-Dzari'ah, a business activity that is essentially permissible can be restricted if it becomes a means of causing harm to society. This study emphasizes the importance of integration between positive law and Islamic legal principles in strengthening the policy of monitoring the distribution and installation of racing exhausts in order to protect public order and welfare.